STRATEGIC CAPABILITIES AND PERFORMANCE OF HALAL FOOD SMES: THE MEDIATING ROLE OF COMPETITIVE ADVANTAGE - Alimatul Farida; Muhamad Ahsan; Burhan Djamaluddin (International Conference on Humanity Education and Society (ICHES), 2026)
Despite the rapid growth of the global halal industry, empirical evidence explaining how internal firm capabilities shape performance outcomes among halal certified small and medium sized enterprises (SMEs) remains limited. Drawing on the Resource- Based Theory (RBT), this study examines the effects of human capital competence, innovation strategy, Islamic financial literacy, and market orientation on the performance of halal food and beverage SMEs, with competitive advantage acting as a mediating mechanism. A quantitative explanatory approach was employed using survey data collected from 278 owners and managers of halal-certified SMEs in Mojokerto, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that all internal capability variables exert positive and significant effects on SME performance. Furthermore, competitive advantage plays a pivotal mediating role by strengthening the indirect relationships between internal resources and performance outcomes. These results extend the Resource-Based Theory by demonstrating that value-based and non-financial internal resources are critical in generating sustainable competitive advantage and enhancing firm performance within the halal SME context, particularly in emerging economies.